Penyimpangan Seksual Tokoh Mubarak dalam Novel Pendosa yang Saleh Karya Royyan Julian: Kajian Sigmund Freud - Milliana; Akhmad Tabrani; Ach. Jazuli (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
This study aims to describe the forms and factors of sexual deviation of Mubarak's character in the novel Pendosa yang Saleh by Royyan Julian with Sigmund Freud's study. This research method is descriptive qualitative. The data in the study are sentences related to the sexual deviation of the main character in the novel Pendosa yang Saleh by Royyan Julian. Data collection techniques are reading, note taking, and data corpus collection. The findings of this study are the form of sexual deviation of the character Mubarak in the novel Pendosa yang Saleh by Royyan Julian in the form of inversion pedophilia unfixed with the aim of fetishism (bisexual). The factor of Mubarak's sexual deviation refers to Sigmund Freud's study, namely the aspects of frustration and trauma.